A Motion‐guided Interface for Modeling 3D Multi‐functional Furniture. (27th November 2021) - Chen, Minchan; Lau, Manfred
Abstract: While non‐expert 3D design systems are helpful for performing conceptual design, most existing works focused on modeling static objects. However, the 3D modeling interfaces can include more interactions between the user and the models that are dynamic (and can be interacted with). In this paper, we propose a 3D modeling system for the conceptual design of interactable multi‐functional furniture. Our contribution is in the design and development of a motion‐guided interface. The key idea is that users should create interactable furniture components as if they are interacting with them with their hands. We conducted a preliminary user study to explore users' preferred hand gestures for creating various dynamic furniture components, implemented a 3D modeling system with the preferred gestures as a basis for the motion‐guided user interface, and conducted an evaluation user study to demonstrate that our user interface is user‐friendly and efficient for novice designers to perform conceptual furniture designs.